2000
DOI: 10.1002/1521-186x(200010)21:7<515::aid-bem5>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

No mutagenic or recombinogenic effects of mobile phone fields at 900 MHz detected in the yeastSaccharomyces cerevisiae

Abstract: Both actively growing and resting cells of the yeast Saccharomyces cerevisiae were exposed to 900-MHz fields that closely matched the Global System for Mobile Communication (GSM) pulsed modulation format signals for mobile phones at specific absorption rates (SAR) of 0.13 and 1.3 W/kg. Two identical anechoic test chambers were constructed to perform concurrent control and test experiments under well-controlled exposure conditions. Using specific test strains, we examined the genotoxic potential of mobile phone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The effects of EMF that have been studied in S. cerevisiae include apoptotic, mutagenic, and recombinogenic effects of RF-EMF [Gos et al, 2000;Markkanen et al, 2004] and gene and protein expression responses to ELF-MF [Binninger and Ungvichian, 1997;Nakasono et al, 2003;Luceri et al, 2005;Sinclair et al, 2006]. cerevisiae has been widely used to explore the biological effects induced by various environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of EMF that have been studied in S. cerevisiae include apoptotic, mutagenic, and recombinogenic effects of RF-EMF [Gos et al, 2000;Markkanen et al, 2004] and gene and protein expression responses to ELF-MF [Binninger and Ungvichian, 1997;Nakasono et al, 2003;Luceri et al, 2005;Sinclair et al, 2006]. cerevisiae has been widely used to explore the biological effects induced by various environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…cerevisiae has been widely used to explore the biological effects induced by various environmental stimuli. The effects of EMF that have been studied in S. cerevisiae include apoptotic, mutagenic, and recombinogenic effects of RF-EMF [Gos et al, 2000;Markkanen et al, 2004] and gene and protein expression responses to ELF-MF [Binninger and Ungvichian, 1997;Nakasono et al, 2003;Luceri et al, 2005;Sinclair et al, 2006]. However, the effects of ELF-MF on cellular gene expression are controversial [Binninger and Ungvichian, 1997;Nakasono et al, 2003;Luceri et al, 2005], and the possible effects of RF-EMF exposure on gene expression in yeast cells remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus microbial mutation assays have returned largely negative results, as have Drosophila melanogaster (fruit fly) in vivo mutation assays (Brusick et al, 1998). Furthermore, RFEMR does not appear to induce DNA strand breaks in murine fibroblasts (Malyapa et al, 1997;Li et al, 2001), human blood cells (Garson et al, 1991;Maes et al, 1997) or the yeast, Saccharomyces cerevisiae (Gos et al, 2000). RFEMR has also been shown to have no efficacy as a tumour promoter in major tissues in mice (Heikkinen et al, 2001;Mason et al, 2001) or rats (Bartsch et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results indicate that modulated RF/MW radiation with a low SAR value did not affect either the rate of gene conversion nor reverse mutations in strain D7. Gos et al 21 reported that mobile phone fields at 900 MHz with SAR of 0.13 and 1.3 W/kg did not exhibit any effect on mutations or recombinations in S. cerevisiae cells either in the absence or presence of genotoxic stress.…”
Section: Discussionmentioning
confidence: 99%